2018
DOI: 10.1002/met.1724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerosol number concentration on precipitation under different precipitation rates

Abstract: Mainly by modifying the number concentration and size of cloud droplets, the dynamic and thermodynamic effects of aerosols are important in the formation of precipitation, but so far different and occasionally opposite responses of precipitation to aerosol concentration have been noted. By conducting two numerical experiments with different aerosol concentrations, the impact of aerosol number concentration on precipitation under different precipitation rates is examined. To this end, the Weather Research and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Interestingly, biomass burning aerosols have an opposite effect to industrial aerosols in some regions. For example, the Amazon region experiences an increase in extreme fire-weather risk in the early 21st century due to biomass burning, possibly linked to inhibited cloud formation, which reduces low-intensity precipitation and increases temperatures 33 , 34 . These findings establish a more nuanced characterization of the anthropogenic impact on extreme fire-weather risk to inform mitigation and adaptation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, biomass burning aerosols have an opposite effect to industrial aerosols in some regions. For example, the Amazon region experiences an increase in extreme fire-weather risk in the early 21st century due to biomass burning, possibly linked to inhibited cloud formation, which reduces low-intensity precipitation and increases temperatures 33 , 34 . These findings establish a more nuanced characterization of the anthropogenic impact on extreme fire-weather risk to inform mitigation and adaptation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Control experiments were first conducted to confirm the precipitation of these metals before introducing the coagulant. It is reported that the rate of precipitation increased with an increase in dissolution rate as the solution became more concentrated [31]. Therefore, little or no reduction in the concentration of Cu and Pb were observed in the acidic medium up to pH 7.20; however, the removal efficiencies obtained from pH 7.20 to 10 might be due to dual mechanisms suggested to be precipitation and adsorption in Figure 5a,b.…”
Section: Effect Of Metals Solution Phmentioning
confidence: 90%
“…ARC is the difference of shortwave (SW) and longwave (LW) fluxes between the top of the atmosphere (TOA) and the surface. ARC has significant impacts on global hydrological sensitivity (Allen and Ingram, 2002), while changes in the energy transport term (δH ) are essential in determining the spatial pattern of precipitation response (Muller and O'Gorman, 2011). Dagan et al (2019) further demonstrated that whether precipitation responses are more correlated with changes in Q or H depends on the latitude considered.…”
Section: Introductionmentioning
confidence: 97%
“…An energetic perspective provides an alternative approach to examine aerosol effects on precipitation, which is referred to as a "top-down" approach. For global scales, in equilibrium, latent heat released from rainfall should be energetically balanced by atmospheric radiative cooling together with surface energy fluxes (Allen and Ingram, 2002;Andrews et al, 2010). Climate forcers, such as greenhouse gases (GHGs) and aerosols, which affect the energy budget, can modify the hydrological responses (Kvalevåg et al, 2013;Stephens and Hu, 2010).…”
Section: Introductionmentioning
confidence: 99%